(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
In this article investigates the semantic aspect of borrowing complex words in English and Uzbek languages within the context of internet discourse. As globalization and digital communication expand, linguistic borrowing has become prevalent, especially in online environments where language barriers blur. Focusing on the semantic evolution of complex borrowed words . Additionally, it investigates the role of internet-mediated communication in facilitating lexical borrowing and semantic innovation. The findings reveal intricate patterns of semantic adaptation, ranging from straightforward transliterations to nuanced semantic extensions. Moreover, the study identifies key factors influencing semantic change, including frequency of usage, community acceptance, and functional equivalence. Overall, this study provides valuable insights into the semantic aspect of borrowing complex words in English and Uzbek within the framework of internet media, offering implications for language planning, cross-cultural communication, and digital discourse analysis.